Analisis Pembelajaran Bilingual Dalam Media Video Menggunakan Pendekatan Kualitatif: Studi Terhadap Strategi Bahasa Guru Dalam Menyampaikan Materi Kepada Siswa Sekolah Dasar - Herowati, Desi Indah; Karini, Vinanda Syafara; Utami, Apriliana Prili; Dani, Anika Rahma; Asfia, Rizka Dwi; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
It is important to introduce English early so that learners have the habit of hearing and understanding its meaning. Embedding bilingual English in the learning process will shape learners' habits to become more familiar with English. The purpose of this study is to analyze the language strategies set by teachers in bilingual learning using video media in elementary schools. The method used in this research is a descriptive qualitative method. The teacher's learning will be analyzed using the learning process instrument, then it will be studied descriptively. The results of the analysis of the bilingual learning video found that the teacher used the Problem-Based Learning model and language strategies in the form of code-switching between English and Indonesian. This strategy helps improve concept understanding, communication skills, and learners' confidence in using a foreign language. The use of video media also supports the bilingual learning process by presenting the material visually and contextually. The conclusion confirms that bilingual learning, when designed in a planned and consistent manner, can strengthen learners' linguistic abilities.